2021
DOI: 10.1016/j.clinbiomech.2021.105480
|View full text |Cite
|
Sign up to set email alerts
|

Use of biomaterials in scaphoid fracture fixation, a systematic review

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 51 publications
(101 reference statements)
0
9
0
1
Order By: Relevance
“…Complication rates were reported to be between 21 and 26%, depending on the graft used [ 23 , 37 , 39 ]. The meta-analysis by Feeley et al [ 2 ] regarding the use of bioabsorbable fixation methods revealed 23% complications, and the SWIFFT study reports 14% in the surgical group [ 14 ]. Reigstad et al [ 24 ] described increased arthrosis around the implanted screw.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Complication rates were reported to be between 21 and 26%, depending on the graft used [ 23 , 37 , 39 ]. The meta-analysis by Feeley et al [ 2 ] regarding the use of bioabsorbable fixation methods revealed 23% complications, and the SWIFFT study reports 14% in the surgical group [ 14 ]. Reigstad et al [ 24 ] described increased arthrosis around the implanted screw.…”
Section: Discussionmentioning
confidence: 99%
“…Keller et al [ 23 ] reported implant irritation which healed only after implant removal. Biomaterials are one alternative, but these materials and their degradation products may interfere with bone healing [ 2 ]. 21,000 hardware removals were performed in Austria in 2016 (personal communication, Gebietskrankenkasse Oberösterreich).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Commercial bioabsorbable implants made from polymers were used for osteosynthesis [ 42 , 43 ]. Polymers such as poly-L-lactic acid (PLLA) or poly-lactic-co-glycolic acid (PLGA) are characterized by high brittleness, a low property of osteoconductivity, and a long degradation rate.…”
Section: Biocompatible Implants Used In Pediatric Osteochondral Fract...mentioning
confidence: 99%